“We Need Supervisors”: Problematic Implementationof Curriculum 2013 among Mathematics Teachers - Setiawan Setiawan; Khairiani Idris (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The development of the curriculum is a dynamic process which aims to comply with the evolvement of knowledge and technology. However, the implementations of the reformed curriculum have been acknowledged to raise various issues. Likewise, among the issues related to the implementation of the Curriculum 2013, known as K13, in Indonesia was teachers’ difficulties, including mathematics teachers. This study aimed at investigating and describing the difficulties faced by junior high school mathematics teachers in implementing K13. The study applied a mixed-method approach involving 66 from a total of 78 junior high school mathematics teachers in Lhokseumawe, Aceh Province, as the study sample. The findings showed that 50%-60% participants encountering difficulties in components of training and socialization of K13, lesson planning, learning activities, and assessment and reporting the learning outcome. Although 93.94% teachers have taken the K13 training, only 56.45% of them sometimes implemented the curriculum in the classrooms. Additionally, the main resource of the difficulties was the ineffectiveness of training and socialization of K13 the teachers had attended. The teachers expected that there would be a learning community or forum as the follow-up action of the training, which can supervise the implementation of K13 in their classes. The directions for further research to improve curriculum implementation were discussed.